Effects of superabsorbent polymers on moisture migration and accumulation behaviors in soil. (10th January 2021) - Wu, Hao; Li, Zhe; Song, Weimin; Bai, Shu
Abstract: Superabsorbent polymer (SAP) is an eco-friendly material in soil and water conservation, agricultural production, and the performance enhancement of cement-based materials. It is well known that moisture migration and accumulation is a prerequisite for the performance deterioration of soil. In this study, SAPs were introduced as an admixture for soil expecting to enhance its ability of accommodating moisture variations. Compaction and dynamic triaxial tests were first conducted to the soil with various contents of SAPs to evaluate their compaction characteristics and mechanical performances. Furthermore, novel moisture migration tests utilizing a self-developed system were performed to quantitatively evaluate the effects of SAPs on improving the moisture migration and accumulation behaviors of soil. Two situations regarding the moisture migration manners typically occur in soil were taken into account: 1) the moisture migration in the formation of liquid state caused by the moisture inside of the soil, and 2) the moisture migration due to the intrusion of external moisture in the formation of liquid and gaseous phase. The findings from the tests showed that within a proper adding content, SAPs could not only improve the uniformity of water distribution in the soil, but improve its workability and compactability. SAP-water gels formed by SAPs also showed potentials on enhancing the cohesion and dynamic modulus of the soil samples under repeat stresses. Due to the water absorption and retention ability, SAPs could significantly restrain the moisture migration and accumulation in the soil; and with an increased content of SAPs, although their moisture contents were higher in the unfrozen zone, smaller moisture contents and less ice lenses/grains could be detected in the frozen zone. Highlights: The feasibility of using SAPs as an admixture or modifier for soil were verified. The effects of SAPs on moisture migration and accumulation behaviors of soil were investigated with specially designed tests. The functions of SAPs on ameliorating the moisture susceptibility of soil were interpreted.